2010
DOI: 10.4014/jmb.0911.11014
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Impaired the Morphological Transition of Candida albicans Under Various Hyphae-Inducing Conditions

Abstract: The ability of the human fungal pathogen Candida albicans to undergo the morphological transition from a single yeast form to pseudohyphal and hyphal forms in response to various conditions is known to be an important for its virulence. Many studies have shown the pharmacological effects of resveratrol, a phytoalexin polyphenolic compound. In this study, we investigated the antifungal activity of resveratrol against C. albicans. Both yeast-form and mycelial growth of C. albicans were inhibited by resveratrol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The effect of resveratrol (3,5,4-trihydroxystilbene), a close analogue of PTE, on C. albicans has been investigated previously (57)(58)(59). However, its antifungal effect was much weaker than PTE.…”
Section: Met14mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of resveratrol (3,5,4-trihydroxystilbene), a close analogue of PTE, on C. albicans has been investigated previously (57)(58)(59). However, its antifungal effect was much weaker than PTE.…”
Section: Met14mentioning
confidence: 99%
“…However, its antifungal effect was much weaker than PTE. More specifically, Okamoto et al revealed that the MIC 50 of resveratrol against C. albicans SC5314 was about 200 g/ml, and resveratrol (Ն40 g/ml) could inhibit the yeast-to-hypha morphological transition of C. albicans (57), while Collado et al (58) and Weber et al (59) reported that resveratrol had no antifungal activity against C. albicans. In this study, we found that PTE has a much stronger antifungal effect against C. albicans than resveratrol, with a MIC 80 of 32 g/ml and a minimal concentration in- hibiting morphological transition of 4 g/ml.…”
Section: Met14mentioning
confidence: 99%
“…With respect to C. albicans, dimorphism plays a crucial role in the pathogenesis, with mycelial shapes being mainly found during a host tissue invasion ( Fig. 2A, B) Okamoto-Shibayama et al, 2010). The compounds exerted an inhibitory effect against the mycelial form of the C. albicans cells.…”
Section: Antimicrobial and Hemolytic Activities Of Styraxjaponoside Amentioning
confidence: 99%
“…While C. albicans does not possess a COX homolog, the fatty acid desaturase OLE2 and the multicopper oxidase FET3 were found to play a role in prostaglandin synthesis (40). Concurrently, several COX inhibitors, including diclofenac sodium, indomethacin, ibuprofen, resveratrol, and eicosatetraynoic acid (ETYA), were shown to block the Y-H transition induced in serum-containing, Lee's or Spider medium at 37°C (3,44,108,136). It is not clear whether or not COX inhibitors affected filamentation by blocking prostaglandin synthesis, given that a direct association between reduced prostaglandin levels and reduced hypha formation was not shown and that C. albicans does not encode a COX homolog.…”
Section: Fatty Acids Eicosanoids and Cyclooxygenase Inhibitorsmentioning
confidence: 99%
“…Moreover, COX inhibitors appeared to reduce viability of C. albicans cells, which may account for their hypha-inhibiting activities (3,36,102). For instance, diclofenac sodium and resveratrol blocked hyphal development but also affected cellular growth (44,108).…”
Section: Fatty Acids Eicosanoids and Cyclooxygenase Inhibitorsmentioning
confidence: 99%